The Correlation Between Serum Chemokines and Clinical Outcome in Patients with Advanced Biliary Tract Cancer - Su Jin Lee; Jung Eun Kim; Seung Tae Kim; Jeeyun Lee; Se Hoon Park; Joon Oh Park; Won Ki Kang; Young Suk Park; Ho Yeong Lim (Translational Oncology, 2018)
BACKGROUND: Biliary tract cancers (BTCs) are known to have a dismal prognosis. A number of chemokines play important roles in the progress of BTCs. However, the serum levels of chemokines in BTCs have not yet been explored. METHODS: The sera of healthy donors (n = 8) and patients with BTCs who were enrolled in second line sunitinib trials (n = 27) were collected. The concentrations of three kinds of chemokines (CXCL5, CXCL8 and CXCL12) were measured using ELISA assay. The median concentrations of chemokines were compared between healthy donors and BTC patients and the role of chemokines as a prognostic biomarker was examined. RESULTS: BTC patients generally had higher serum levels of CXCL5 and CXCL12 compared to healthy donors. Patients with cholangiocarcinoma showed significantly higher levels of serum CXCL12 than patients with gallbladder cancer. In survival analysis, only CXCL12 level showed a prognostic impact on overall survival (median OS: 6.9 vs. 0.9 months in low CXCL12 vs. high CXCL12, respectively; P = .008). High CXCL5 levels were also correlated with poor survival without statistical insignificance (median OS: 6.2 vs. 2.0 months in low CXCL5 vs. high CXCL5, respectively; P = .070). CONCLUSIONS: There was a significant difference in OS according to the level of CXCL12, suggesting that serum CXCL12 levels may be a useful surrogate marker for clinical outcome in advanced BTCs.